Expansão da educação superior: um estudo sobre trabalho docente no Campus Pontal da Universidade Federal de Uberlândia (2006-2012) - Coelho, Luciana Zacharias Gomes Ferreira (2015)
In face of a globalized society, dominated by technology and capital in all its dimensions, the less privileged seek in formal higher education the possibility of ascension and self-realization. It should be noted that the expansion has been taking place in public higher education, which includes restructuring investment in existing universities, creation of new university centers and various forms of entry, as well as other measures; but it is necessary to check whether such expansion has occurred without creating precarious labor condition of those involved in the process, like the teachers, who may encounter a lack of basic resources to offer an education that ensures not only quantity, but also quality In this sense, this study aims to understand some aspects of the phenomenon of expansion, especially in the context of the Federal University of Uberlândia s internalization. The creation of the Campus Pontal, located in the city of Ituiutaba (MG), refers to the first experience of this institution regarding the implementation of a physical and organizational structure out of its headquarters, in order to meet regional demands of free and quality education in this city and its surroundings. The scope of this study was to investigate the perception of teachers allocatd there about the working conditions which were offered in such expansionist context, the exogenous and endogenous factors that that triggered the internalization of the institution in the city of Ituiutaba and sought to identify and discuss the main aspects related to the working conditions of teachers in the new campus outside of headquarters.